Mapping stem rust resistance genes in ‘Kingbird’ - Gambone, Katherine (Kansas State University, 2016)
Stem rust, caused by the fungus Puccinia graminis f. sp. tritici, has historically been one of the most important diseases of wheat. Although losses have been much reduced in the last fifty years, new highly virulent races of the pathogen have recently emerged in East Africa. These new races are virulent on nearly all of the currently deployed resistance genes and therefore pose a serious threat to global wheat production. The spring wheat variety ‘Kingbird’ is thought to contain multiple quantitative trait loci (QTLs) that provide durable, adult-plant resistance against wheat stem rust. Stem rust-susceptible Kansas winter wheat line ‘KS05HW14’ was backcrossed to Kingbird and 379 recombinant lines were advanced to BC₁F₅ and then increased for testing. The lines were screened for stem rust resistance in the greenhouse and field in Kansas and in the field in Kenya over multiple years. We identified 16,237 single nucleotide polymorphisms (SNPs) with the Wheat 90K iSelect SNP Chip assay. After filtering for marker quality, linkage maps were constructed for each wheat chromosome. Composite interval mapping and multiple-QTL mapping identified seven QTLs on chromosome arms 2BL, 2DS, 3BS, 3BSc, 5DL, 7BL, and 7DS. Six QTLs were inherited from Kingbird and one QTL on 7BL was inherited from KS05HW14. The location of the QTL on 2BL is approximately at locus Sr9, 3BS is at Sr2, 3BSc is at Sr12, and 7DS is at Lr34/Yr18/Sr57. Although no QTL was found on 1BL, the presence of resistance gene Lr46/Yr29/Sr58 on 1BL in both parents was indicated by the gene-specific marker csLV46. QTLs on 2DS and 5DL may be related to photoperiod or vernalization genes. Pairwise interactions were only observed with race QFCSC, most notably occurring with QTLs 2BL and 3BSc. These results confirm that there are multiple QTLs present in Kingbird. Ultimately, the identification of the QTLs that make Kingbird resistant will aid in the understanding of durable, non-race-specific resistance to stem rust of wheat.
Keywords: Stem Rust; QTL Mapping; MQMWheat